Performance evaluation of electronic inductor based adjustable speed drives with respect to line current interharmonics - Soltani, H.; Davari, P.; Blaabjerg, F.; Zare, Firuz (2017)
Electronic Inductor (El)-based front-end rectifiers have a large potential to become the next generation of Active Front End (AFE) topology used in many applications including Adjustable Speed Drives (ASDs) for systems having unidirectional power flow. The EI-based ASD is mostly attractive due to its improved harmonic performance compared to a conventional ASD. In this paper, the input currents of the EI-based ASD are investigated and compared with the conventional ASDs with respect to interharmonics, which is an emerging power quality topic. First, the DC-link oscillations generation process is analyzed at the inverter level under balanced and unbalanced load conditions, where they are considered as main causes of the interharmonic distortions in the ASD applications. Thereafter, the key role of the EI at the DC stage is investigated in terms of high impedance and current harmonics transfer, and it is compared with the conventional passive filter performance. It is shown that the EI will reduce low-frequency oscillations coming from the load side, and consequently it will give rise to lower-amplitude interharmonics in the input current of the drive. The obtained experiments and simulations for both EI-based and conventional ASD systems verify the proposed theoretical analysis in determining the line input current interharmonics.